Implementation of Physical Fitness Measurement Based On Vald Performance With The Nordbord Tool at Askot PSSI Football School, West Jakarta - Putri, Sarah Aulia; Fauzia, Syifa; Lestari, Dita Asri; Setiawan, Muhammad Arief (UNIVERSITAS NEGERI MAKASSAR, 2024)
Physical tests are an important part of forming high-achieving athletes and are the main element in a coach's training program. This study aims to: (1) Produce a physical fitness test based on Vald Performance with the Nordbord tool for football school athletes at Askot PSSI West Jakarta; (2) Determine the feasibility and response to the use of Vald Performance with the Nordbord tool by athletes; and (3) Analyze the results of athletes' physical abilities using the test. This study uses a qualitative method with descriptive analysis. The test development process involves validation tests and feasibility tests by experts in the field of sports technology. The Nordbord tool is used to measure the strength and imbalance of the hamstring muscles in various positions, which are important indicators of athlete performance. The results of the study show that the Vald Performance-based fitness test with the Nordbord tool received good validation from experts and positive responses from users. This test is considered effective and practical for identifying the level of strength and potential for hamstring muscle injury in football athletes. In addition, the test results provide accurate quantitative data to evaluate the physical condition of athletes individually, making it easier for coaches to design more specific and targeted training programs. The use of the Nordbord tool also shows great potential in improving the quality of athlete coaching in the soccer school environment. This study contributes to the development of technology-based physical fitness testing methods that can be widely applied to other sports.